Liver carcinoid treated palliatively by radiotherapy – a case report - Skowronek, Janusz; Nyczak, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2000)
Low radiation tolerance of the liver is the limiting factor in using any form of radiotherapy to control hepatic neoplasms. In some centres palliative radiotherapy of cancer changes in liver is an object of clinical tests. More often livers complications after radiotherapy of neoplasms localised in upper part of abdominal cavity is investigated. A introduced a case of isolated liver carcinoid palliatively is demonstrated irradiated. Irradiating began after chemotherapy and in regard on slow course of disease and lack of other neoplastic focus. After application of 2 800 cGy (with fraction dose 200 cGy) on entire liver one ascertained partial remission of tumours in seeing subsequent computer tomography investigations was observed. Patient survived 13 months and died of dissemination of neoplasm to other organs. Published results of radiotherapy of liver neoplasms are discussed.